2015
DOI: 10.1097/jsm.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Muscle Architecture of the Biceps Femoris and Vastus Lateralis by Ultrasound After a Chronic Stretching Program

Abstract: To describe changes in the VL and BF muscle tendon unit using US after a long-term stretching program to identify which structures are responsible for ROM increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
7
55
3
Order By: Relevance
“…These studies report a range of ICCs from 0.78 to 0.97 (8,11,30), which, at the upper end, is similar to values reported in the present study. In two of these studies, %TE for the assess ment of the BF|h architecture is also reported, with values ranging from 2.15% to 9.7%, with the current study re porting values ranging from 1.6% to 4.9% (11,19). Only one study has investigated the reliability of ultrasonography of the BFih during an MVIC (100% of maximum); however, the ICC reported was poor (0.78) (II).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These studies report a range of ICCs from 0.78 to 0.97 (8,11,30), which, at the upper end, is similar to values reported in the present study. In two of these studies, %TE for the assess ment of the BF|h architecture is also reported, with values ranging from 2.15% to 9.7%, with the current study re porting values ranging from 1.6% to 4.9% (11,19). Only one study has investigated the reliability of ultrasonography of the BFih during an MVIC (100% of maximum); however, the ICC reported was poor (0.78) (II).…”
Section: Discussionsupporting
confidence: 92%
“…Imaging maximal contractions is diffi cult because of the inability of participants to maintain a smooth contraction long enough to allow the images to be captured. The combined findings from this article and from previous work (11) suggest that the assessment of BFih ar chitecture during active contractions is reproducible but not for maximal contractions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Some studies investigating the effects of 90s and 120s stretching volume per session observed ROM gains without modifying the muscle fascicle length, assessed by ultrasound (Konrad & Tilp, 2014;Lima et al, 2015). Also, the same studies did not find isometric and passive torque changes when 90s and 120s stretching volume was performed.…”
Section: Dicussionmentioning
confidence: 84%
“…Asymptomatic volunteers were chosen in order not to compound the variables with the effects of PFP on the individuals' ability to carry out the exercises. The application of ultrasound in investigations into skeletal muscle architecture has been demonstrated in multiple studies (e.g., [23,24]). The method used here has been validated [25], and has been used in previous investigations into the VMO [18,[26][27][28][29].…”
Section: Physical Therapy and Rehabilitationmentioning
confidence: 99%